Between Vision and Reality: A Study of Scientists' Views on Citizen Science. (3rd October 2017) - Golumbic, Yaela N.; Orr, Daniela; Baram-Tsabari, Ayelet; Fishbain, Barak
Increased interest in public engagement with science worldwide has resulted in the growth of funding opportunities for scientists in the rapidly expanding field of citizen science. This paper describes a case study based on interviews and observations, including a six-month field diary, of ten scientists who engaged in a citizen science project to receive funding for their scientific research. It examines how these scientists perceived their commitment to the public, and it explores relationships between the ways that citizen science is defined and presented in the literature and the ideas that scientists in this project have about citizen science. The findings indicate that these scientists were motivated mostly by their interest in promoting scientific research and obtaining prestigious funding. Many of the scientists also found it difficult to accept the idea that the public can make actual contributions to science. Although the scientists acknowledged the advantages and benefits of citizen participation for the public, they had no desire to actively engage with the public and would rather conduct a traditional study without the public's involvement. Exposing scientists to public engagement and citizen science concepts, especially at early stages of their scientific carrier, could help overcome barriers and encourage scientists to further engage the public in such initiatives.